1991
DOI: 10.1016/s0735-1097(10)80239-6
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter embolization in the treatment of coronary artery fistulas

Abstract: Seven patients with a coronary artery fistula underwent percutaneous transcatheter embolization (five were male and two female; the age range was 2 to 67 years [median 17]). Three patients were symptomatic. The left to right shunt ranged from 1.6 to 2.6:1. In six patients, the fistula was an isolated congenital anomaly; in one, it was acquired. The fistula arose from branches of the left (n = 5) and right (n = 2) coronary arteries and drained to the right ventricle (n = 2), right atrium (n = 2), coronary sinus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
136
0
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 220 publications
(137 citation statements)
references
References 14 publications
0
136
0
1
Order By: Relevance
“…Surgical closure usually is performed on a beating heart from the epicardial surface, is associated with low mortality and morbidity, and has excellent immediate and long-term outcomes. 81 Various transcatheter occlusion techniques have been used [82][83][84] with excellent outcomes for fistulas with shorter, less tortuous courses.…”
Section: Indications For Interventionmentioning
confidence: 99%
“…Surgical closure usually is performed on a beating heart from the epicardial surface, is associated with low mortality and morbidity, and has excellent immediate and long-term outcomes. 81 Various transcatheter occlusion techniques have been used [82][83][84] with excellent outcomes for fistulas with shorter, less tortuous courses.…”
Section: Indications For Interventionmentioning
confidence: 99%
“…3,16,17) Although several complications such as T-wave inversion on an electrogram, embolization of the coil to the pulmonary artery, and transient arrhythmias were experienced in 30% of patients, 3,16) complete closure of CAVF was obtained in 78% to 82% of patients by transcatheter embolization. 3,17) However, a retrospective review to determine the comparative therapeutic efficacy of operation and coil embolization showed that coil embolization was possible, at most, in 6 (38%) of 16 patients, 16) and has indicated that the requirements for satisfactory coil embolization of a CAF include the ability to safely cannulate the branch coronary artery that supplies the fistula, the absence of large branch vessels that can be inadvertently embolized, the presence of a single, narrow restrictive drainage site into the cardiac chamber or vessel, and the absence of multiple fistulous connections. 3,16,17) According to these results, transcatheter embolization is considered to be a reasonable alternative to standard surgical closure in a selected group of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the actual successful rate for coil embolization is lower than expected and in order to obtain a reliable outcome, the indication must be strict, as outlined by Mavroudis et al: (1) able to safely cannulate the branch coronary artery that supplies the fistula, (2) absence of large branch vessels that can be inadvertently embolized, (3) presence of a single, narrow, restrictive drainage site into the cardiac chamber or vessels, and (4) absence of multiple fistulous communications. 6 Fortunately, the present case had all these requirements.…”
Section: Discussionmentioning
confidence: 99%